Method for producing dispersion liquid, dispersion liquid, and method for producing laminate
The liquid composition of tetrafluoroethylene polymer particles and liquid dispersion medium is treated by a wet bead mill, which solves the problems of low dispersion and poor operability, and achieves high stability of the dispersion liquid and excellent performance of the polymer layer.
Patent Information
- Application Number
- CN202380046236.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-04-14
- Publication Date
- 2025-02-07
AI Technical Summary
The surface tension of tetrafluoroethylene polymers is low, resulting in low dispersion of particles, high equipment versatility and substrate selectivity when used, but their operability is easily reduced, and the productionability and dispersion of the prior art are limited. .
The liquid composition of tetrafluoroethylene polymer particles with a liquid density of 1.15 to 1.5 g/cm3 and a liquid dispersion medium was processed by a wet bead mill. The average particle size of the control particles was less than 10 μm and the specific surface area was between 1 to 25 m2/ Within the range of g, the content is greater than 30 mass%, and a surfactant and a viscosity regulator are added to the dispersion.
The obtained dispersion has excellent dispersion stability and operability, and the formed polymer layer has good heat resistance, electrical characteristics and surface appearance. In particular, its surface appearance is excellent, which reduces tiny defects and improves the overall shape. performance.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a dispersion containing tetrafluoroethylene polymer particles, and a method for producing the dispersion and a laminate. Background Art
[0002] In recent years, in order to cope with the high speed and high frequency of mobile communication devices such as mobile phones, the insulating layer of the printed circuit board of the communication device is required to have a polymer material with a low dielectric constant and a low dielectric loss tangent, and tetrafluoroethylene polymers have attracted much attention. As a material for forming an insulating layer containing such a polymer, a dispersion containing tetrafluoroethylene polymer particles and a liquid dispersion medium is known. Patent document 1 proposes a method for producing an aqueous dispersion containing microparticles of tetrafluoroethylene polymer, wherein tetrafluoroethylene polymer particles having an average particle size of 60 μm or less obtained by dry pulverization are dispersed in an aqueous medium and passed through a passage of a specific width under a specific pressure (wet jet mill). Prior art literature Patent Literature
[0003] Patent Document 1: Japanese Patent Application Publication No. 2008-260864 Summary of the invention Technical problem to be solved by the invention
[0004] The surface tension of tetrafluoroethylene polymers is low, so the dispersibility of their particles is low. If the dispersion liquid is aqueous, the versatility of the equipment required for its use and the selectivity of the substrate as the object of coating, etc. are high, but since the dispersion liquid is easy to foam, its operability is easy to decrease. The method of Patent Document 1 is not only applicable to a limited number of dispersion forms, but also has low productivity. In particular, since particles in an aqueous medium are collided at high speed under high shear conditions to obtain particles of several μm, coarse particles may be generated in the obtained aqueous dispersion, and such coarse particles are also likely to cause foaming. Therefore, the surface of a molded object such as a polymer layer formed from such an aqueous dispersion is prone to micro defects, which may damage its surface appearance. The present inventors have found that, if a liquid composition comprising tetrafluoroethylene polymer particles and a liquid dispersion medium and having a liquid density within a specific range is treated by a wet bead mill, a dispersion liquid in which the formation of coarse particles is suppressed, the dispersion state and dispersion stability are excellent, the foaming is suppressed, and the dispersion liquid is easy to operate can be obtained. In addition, it is found that the formed article such as a polymer layer formed by the dispersion liquid has excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) brought by the tetrafluoroethylene polymer, and in particular, its surface appearance is excellent, thereby achieving the present invention. An object of the present invention is to provide a method for producing a dispersion comprising tetrafluoroethylene polymer particles and a liquid dispersion medium, wherein the formation of coarse particles is suppressed and the dispersion stability and handleability are excellent, the dispersion, a method for producing a laminate having a polymer layer formed from the dispersion, and the laminate. Technical solutions adopted to solve technical problems
[0005] The present invention has the following technical contents. [1] A method for producing a dispersion liquid, comprising: using a wet bead mill to grind a liquid having a density of 1.15 to 1.5 g / cm 3 A liquid composition containing particles of a tetrafluoroethylene-based polymer and a liquid dispersion medium is treated to obtain a dispersion containing particles of the tetrafluoroethylene-based polymer. [2] The method according to [1], wherein the average particle size of the tetrafluoroethylene polymer particles is less than 10 μm and the specific surface area is 1 to 25 m 2 / g. [3] The production method according to [1] or [2], wherein the content of the tetrafluoroethylene polymer particles is greater than 30% by mass. [4] The production method according to any one of [1] to [3], wherein the liquid dispersion medium is at least one selected from the group consisting of water, amides, ketones, and esters. [5] The production method according to any one of [1] to [4], wherein the liquid composition further contains a water-soluble solvent having a surface tension of 20 to 30 mN / m. [6] The production method according to any one of [1] to [5], wherein the viscosity of the liquid composition is 100 to 10,000 mPa·s. [7] The production method according to any one of [1] to [6], wherein the surface tension of the liquid composition is 15 to 45 mN / m. [8] The production method according to any one of [1] to [7], wherein the liquid composition is prepared by mixing a powder of the tetrafluoroethylene polymer with the liquid dispersion medium. [9] The production method according to [8], wherein a degassing treatment is performed during the preparation of the liquid composition.
[10] The production method as described in any one of [1] to [9], wherein the treatment performed by the wet bead mill uses grinding beads with a diameter of less than 2 mm, and is selected from any one of a batch type, a through type or a circulating type bead mill.
[11] The production method according to any one of [1] to
[10] , wherein the dispersion after the wet bead mill treatment is further mixed with at least one of a liquid dispersion medium, an aromatic polymer, or an inorganic filler.
[12] A dispersion obtained by a wet bead mill, wherein the concentration of particles having a particle size of 60 μm or more as measured by a particle counter is less than 1,000 particles / ml, and the dispersion comprises particles of a tetrafluoroethylene polymer and a liquid dispersion medium.
[13] The dispersion according to
[12] , wherein the content of the tetrafluoroethylene polymer particles is greater than 30% by mass and less than 75% by mass.
[14] A method for producing a laminate, comprising placing a dispersion obtained by the method described in any one of [1] to
[11] on a substrate surface and heating the dispersion to form a polymer layer containing the tetrafluoroethylene polymer, thereby obtaining a laminate having a substrate layer composed of the substrate and the polymer layer in sequence.
[15] The manufacturing method as described in
[14] , wherein the substrate is a polyimide film, which contains at least two diamine units derived from 1,4-bis(4-aminophenoxy)benzene and 4,4'-diaminobenzanilide, has a dielectric constant of less than 3.5 at 5.8 GHz, a dielectric loss tangent of less than 0.006, a water absorption of less than 1.2%, and a linear expansion coefficient of 2 to 18 ppm / °C at 50 to 200°C. Effects of the Invention
[0006] According to the present invention, a dispersion liquid having suppressed formation of coarse particles, excellent dispersion stability and operability can be obtained. This dispersion liquid can form a formed article such as a coating film having excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) brought by a tetrafluoroethylene polymer, especially excellent surface appearance, and specifically, it can form a laminate having a polymer layer formed by the dispersion liquid. DETAILED DESCRIPTION
[0007] The following terms have the following meanings. The average particle size (D50) is the volume-based cumulative 50% diameter of particles or fillers obtained by laser diffraction and scattering. That is, the particle size distribution is measured by laser diffraction and scattering, and the cumulative curve is obtained with the total volume of the particle group as 100%, and the particle size at the point where the cumulative volume reaches 50% on the cumulative curve. The D50 of particles or fillers is determined by dispersing the particles in water and analyzing the particles using a laser diffraction / scattering particle size distribution analyzer (LA-920 analyzer manufactured by Horiba, Ltd.). The “average particle size (D90)” is a volume-based cumulative 90% diameter of particles obtained in the same manner as D50. The “specific surface area of particles or fillers” is a value calculated by measuring particles using a gas adsorption (constant volume method) BET multipoint method, and is determined using NOVA4200e (manufactured by Quantachrome Instruments). The "melting temperature" refers to the temperature corresponding to the maximum value of the melting peak of a polymer measured by differential scanning calorimetry (DSC). The “glass transition temperature (Tg)” is a value measured by analyzing a polymer using a dynamic viscoelasticity measurement (DMA) method. The "viscosity" was determined by measuring the composition using a B-type viscometer at 25°C and a rotation speed of 30 rpm. The measurement was repeated 3 times, and the average of the 3 measured values was taken. The "thixotropic ratio" is a value calculated by dividing the viscosity η1 of the composition measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement was repeated 3 times, and the average of the 3 measured values was taken. The "surface tension" of a solvent or solution is a value measured by the Wilhelmy method at 25°C using a surface tension meter. The "HLB (Hydrophilic-Lipophilic Balance) value" of a surfactant is a value determined by the Griffin method and defined by the following calculation formula. HLB value = 20 x [sum of chemical formula weights of hydrophilic moieties] / molecular weight The "unit" in a polymer refers to an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or a unit in which a part of the unit is converted into another structure by treating the polymer. Hereinafter, the unit based on monomer a is also referred to as "monomer a unit".
[0008] The production method of the present invention (hereinafter also referred to as "this method") is to use a wet bead mill to grind a liquid having a density of 1.15 to 1.5 g / cm 3 A method of obtaining a dispersion liquid containing particles of a tetrafluoroethylene-based polymer (hereinafter also referred to as "F polymer") by treating a liquid composition containing particles of the tetrafluoroethylene-based polymer (hereinafter also referred to as "F particles") and a liquid dispersion medium.
[0009] According to this method, the formation of coarse particles can be obtained to be suppressed, the dispersion stability and the excellent operability of the dispersion liquid. The formed objects such as the coating (polymer layer) formed by this dispersion liquid are excellent in the properties such as the heat resistance, electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) brought by tetrafluoroethylene polymers, particularly its excellent surface appearance. In addition, in this specification, so-called "excellent surface appearance" includes any one of the excellent surface smoothness including "surface roughness is few" or "surface without stripes, cracks or defects, etc." or the excellent appearance observed by the visual recognition or analysis equipment. The reasons why the dispersion obtained by this method has excellent dispersion stability due to suppressed formation of coarse particles and excellent handleability due to suppressed foaming are not necessarily clear, but are considered to be as follows.
[0010] The surface tension of F polymer is low, and it is not easily wetted by the liquid dispersion medium, and it is easy to fibrillate and deteriorate. Therefore, in the dispersion liquid containing F particles, it is difficult to adjust the balance between the wettability of the F particle surface and the agglomeration of the F particles. Therefore, the formation of coarse particles in the liquid causes a decrease in dispersion stability, the decrease in operability due to foaming, and the coating film (polymer layer) formed by the dispersion liquid is prone to poor appearance or defects. The wet bead mill treatment of this method can also be regarded as a dispersion treatment. That is, by subjecting the liquid composition containing F particles to a wet bead mill treatment, the shear force caused by the speed difference generated when the grinding beads move in the fluid, and the friction and collision caused by the rotational shear force caused by the angular velocity difference generated by the rotation of the grinding beads eliminate the agglomeration of the F particles. At this time, if the liquid density of the liquid composition to be treated is controlled within a specified range, it is believed that this effect will be appropriately dispersed and mitigated due to the mass of the flowing liquid composition, and the deterioration of the F polymer is suppressed while the high wetting of the F particles is promoted. It is presumed that as a result, a dispersion liquid in which the formation of coarse particles is suppressed and the foaming property is suppressed and easy to operate is obtained. This tendency is particularly noticeable when the average particle size (D50) of the F particles in the liquid composition is less than 10 μm or when the specific surface area is specified. In addition, it is particularly noticeable when the viscosity or surface tension of the liquid composition, or both, are controlled within a specific range. Furthermore, if the liquid composition contains a water-soluble solvent having a surface tension within a specific range, the surface of the F particles is easily wetted and the agglomerates of the F particles are easily broken, and the defoaming effect of the dispersion is easily improved, and the foaming of the resulting dispersion is easily further suppressed.
[0011] The F polymer of the present invention is a polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE"). The polymer F may be heat-fusible or non-heat-fusible. Here, the heat-fusible polymer refers to a polymer having a temperature at which the melt flow rate is 1 to 1000 g / 10 minutes under a load of 49 N. In addition, the non-heat-fusible polymer refers to a polymer having no temperature at which the melt flow rate is 1 to 1000 g / 10 minutes under a load of 49 N. The melting temperature of the heat-melting polymer F is preferably 180°C or higher, more preferably 200°C or higher. In this case, the heat resistance of a molded product such as a coating film (polymer layer) formed from the present dispersion is likely to be excellent. The melting temperature of the polymer F is preferably 325°C or lower, more preferably 320°C or lower. From the viewpoint that the above-mentioned mechanism of action is more likely to be manifested, the melting temperature of the F polymer is preferably 180°C to 325°C, more preferably 200°C to 325°C, and even more preferably 200 to 320°C.
[0012] The glass transition temperature of the F polymer is preferably 50° C. or higher, more preferably 75° C. or higher. The glass transition temperature of the F polymer is preferably 150° C. or lower, more preferably 125° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a drop of a mixed solution for wetting tension test specified in JIS K6768 (manufactured by Wako Pure Chemical Industries, Ltd.) on a flat plate made of the F polymer.
[0013] The F polymer is preferably polytetrafluoroethylene (PTFE), a polymer containing TFE units and ethylene-based units (ETFE), a polymer containing TFE units and propylene-based units, a polymer containing TFE units and perfluoro(alkyl vinyl ether) (PAVE)-based units (PAVE units) (PFA), a polymer containing TFE units and hexafluoropropylene-based units (FEP), more preferably PFA or FEP, and further preferably PFA. As the F polymer, one of these polymers may be used alone, or two or more of them may be used in combination, and may further contain units based on other comonomers. Examples of PTFE include low molecular weight PTFE and modified PTFE. As PAVE, CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE") is preferred, and PPVE is more preferred.
[0014] The F polymer preferably has oxygen-containing polar group, more preferably has hydroxyl-containing group or contains carbonyl group, further preferably has carbonyl-containing group. In this case, the dispersion liquid that this method obtains is easily excellent in dispersion stability and operability. In addition, the formed objects such as the coating film (polymer layer) formed by this dispersion liquid are easily excellent in physical properties such as heat resistance, electrical characteristics (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) or its surface appearance. As the hydroxyl group, an alcoholic hydroxyl group is preferred, and -CF2CH2OH or -C(CF3)2OH is more preferred. As the carbonyl-containing group, preferred are carboxyl group, alkoxycarbonyl group, amide group, isocyanate group, carbamate group (-OC(O)NH2), acid anhydride residue (-C(O)OC(O)-), imide residue (-C(O)NHC(O)-, etc.) or carbonate group (-OC(O)O-), and more preferred is acid anhydride residue. In the case where the F polymer has an oxygen-containing polar group, the number of the oxygen-containing polar groups in the F polymer is preferably 1×10 6 The number of oxygen-containing polar groups in the polymer F is preferably 10 to 5000, and more preferably 100 to 3000. The number of oxygen-containing polar groups in the polymer F can be quantified based on the composition of the polymer or by the method described in International Publication No. 2020 / 145133.
[0015] The oxygen-containing polar group may be contained in the monomer-based unit in the F polymer or in the terminal group of the F polymer main chain, and the former form is preferred. As the latter form, there can be mentioned F polymers having oxygen-containing polar groups as terminal groups derived from polymerization initiators, chain transfer agents, etc., and F polymers obtained by subjecting F polymers to plasma treatment or ionizing radiation treatment.
[0016] The F polymer is preferably a polymer having a carbonyl group containing a TFE unit and a PAVE unit, and more preferably a polymer containing a TFE unit, a PAVE unit, and a unit based on a monomer having a carbonyl group and containing 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol% of these units in order relative to all units. As a specific example of such a F polymer, a polymer described in International Publication No. 2018 / 16644 can be cited. As the monomer having a carbonyl group, itaconic anhydride, citraconic anhydride or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH") is preferred, and NAH is more preferred.
[0017] In the present invention, the D50 of the F particles is preferably less than 10 μm, more preferably 1 μm or more and less than 10 μm. The F particles may be solid particles or non-hollow particles. The F particles may be secondary particles formed by nanometer-level microparticles. The D50 of the F particles is preferably 1.0 μm or more, more preferably 1.5 μm or more. The D50 of the F particles is preferably 6 μm or less, more preferably 5 μm or less. Furthermore, D90 of the F particles is preferably 8 μm or less, more preferably 6 μm or less. When D90 of the F particles is below the upper limit, the above-mentioned mechanism of action is more likely to be manifested, and a dispersion having a small number of coarse particles is more likely to be obtained.
[0018] The specific surface area of the F particles is preferably 1 to 25 m 2 / g, more preferably 6 to 15 m 2 / g. In this case, the dispersion liquid that this method obtains is easily excellent in dispersion stability and operability. In addition, formed articles such as the coating film (polymer layer) formed by this dispersion liquid are easily excellent in physical properties such as heat resistance, electrical characteristics (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) or its surface appearance. It is considered that when the specific surface area of the F particles is within the above range, the surface of the F particles is easily wetted by the liquid dispersion medium or the water-soluble solvent having a surface tension within a specific range described below, and the aggregates of the F particles are easily broken up, making it easier for the above mechanism of action to manifest.
[0019] The F particles are particles containing an F polymer, and preferably consist of an F polymer. The F particles are more preferably particles of a hot-melt F polymer having an oxygen-containing polar group with a melting temperature of 200 to 325° C. In this case, the above-mentioned action mechanism is more likely to be manifested, and aggregation of the F particles is also easily suppressed. The F particles may further contain a resin or inorganic compound other than the F polymer, and may form a core-shell structure with the F polymer as the core and the resin or inorganic compound other than the F polymer as the shell, or may form a core-shell structure with the F polymer as the shell and the resin or inorganic compound other than the F polymer as the core. Here, examples of the resin other than the F polymer include aromatic polyester, polyamideimide, polyimide, and maleimide, and examples of the inorganic compound include silicon dioxide and boron nitride.
[0020] The F particles may be used alone or in combination of two or more. In addition, F particles can be mixed with particles of non-thermal-fusible tetrafluoroethylene polymers. As F particles, particles of heat-fusible F polymers with a melting temperature of 200 to 325°C are preferred, and particles of heat-fusible F polymers with oxygen-containing polar groups with a melting temperature of 200 to 325°C are more preferred. In addition, as particles of non-thermal-fusible tetrafluoroethylene polymers, particles of non-thermal-fusible PTFE are preferred. In this case, the agglomeration inhibition effect brought about by the particles of the heat-fusible F polymer and the retention effect brought about by the fibrillation of the non-thermal-fusible tetrafluoroethylene polymer reach a balance, and the dispersibility of the dispersion obtained by this method is easily improved. In addition, in the formed articles such as the coating (polymer layer) formed therefrom, the electrical properties of the non-thermal-fusible tetrafluoroethylene polymer are easily highly manifested.
[0021] In the present method, the liquid dispersion medium constituting the liquid composition is preferably at least one selected from the group consisting of water, amides, ketones, and esters. Examples of the amide include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropionamide, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone. Examples of the ketone include acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-amyl ketone, methyl isoamyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, and cycloheptanone. Examples of the ester include methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethyl 3-ethoxypropionate, γ-butyrolactone, and γ-valerolactone. These may be used alone or in combination of two or more. The liquid dispersion medium is preferably a mixture of a water-soluble solvent having a surface tension within a specific range described below and water, and the liquid dispersion medium is more preferably water.
[0022] In this method, the liquid composition may further contain a surfactant. As the surfactant, a nonionic surfactant is preferred. Examples of the nonionic surfactant include glycol-based surfactants, acetylene-based surfactants, silicone-based surfactants, and fluorine-based surfactants. Specific examples of nonionic surfactants include the "FTERGENT" series (manufactured by NEOUS Co., Ltd.), the "SURFLON" series (manufactured by AGC Seimi Chemical Co., Ltd.), the "MEGAFACE" series (manufactured by DIC Corporation), the "UNIDYNE" series (manufactured by Daikin Industries, Ltd.), "BYK-347", "BYK-3 "49", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Chemical Japan Co., Ltd.), "KF-6011", "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.), "Tergitol" series ("Tergitol TMN-100X" manufactured by The Dow Chemical Company, etc.).
[0023] Among them, nonionic surfactants having hydroxyl groups in the hydrophilic part are preferred, silicone surfactants having an HLB value of 10 or more are preferred, and polyoxyalkylene-modified dimethylsiloxanes having a polyoxyalkylene structure as the hydrophilic part and a polydimethylsiloxane structure as the hydrophobic part are more preferred. The polyoxyalkylene-modified dimethylsiloxane may have a polydimethylsiloxane unit (-(CH3)2SiO 2 / 2 -), may have a polydimethylsiloxane unit in the side chain, or may have a polydimethylsiloxane unit in both the main chain and the side chain. The polyoxyalkylene-modified polydimethylsiloxane is preferably a polyoxyalkylene-modified polydimethylsiloxane having a main chain containing a dimethylsiloxane unit and a side chain containing an oxyalkylene unit, or a polyoxyalkylene-modified polydimethylsiloxane having a main chain containing a dimethylsiloxane unit and a main chain terminal containing an oxyalkylene unit. The oxyalkylene groups contained in the polyoxyalkylene-modified dimethylsiloxane may be composed of only one type of oxyalkylene groups or may be composed of two or more types of oxyalkylene groups. In the latter case, different types of oxyalkylene groups may be connected randomly or in blocks.
[0024] The surfactant may be used alone or in combination of two or more. The content of the surfactant in the dispersion obtained by this method is preferably in the range of 1 to 15 parts by mass, more preferably 3 to 10 parts by mass, based on 100 parts by mass of the F particles.
[0025] In this method, the liquid composition may further contain a viscosity modifier. When the viscosity modifier is contained, the dispersion state and dispersion stability of the dispersion obtained by this method are easily improved. In addition, the rheological properties are improved, the operability such as the film-forming property of the dispersion obtained by this method is easily improved, and a thick polymer layer is more easily formed. The viscosity modifier is preferably at least one selected from polar vinyl polymers and polysaccharides. In addition, the polar vinyl polymer refers to an vinyl polymer having a polar functional group in the main chain or side chain of the polymer, and examples of the polar functional group include ether bonds, ester bonds, amide bonds, imide bonds, thioether bonds, sulfide bonds, disulfide bonds, carbonyl-containing groups, hydroxyl-containing groups, mercapto groups, sulfhydryl groups, sulfonyl groups, sulfonyloxy groups, amino groups, and amide groups.
[0026] Preferred polar vinyl polymers include vinyl alcohol polymers such as polyvinyl alcohol, vinyl pyrrolidone polymers such as polyvinyl pyrrolidone, acrylic polymers such as polyacrylic acid, and carboxyvinyl polymers such as carboxyvinyl polymer. Examples of the vinyl alcohol polymer include polyvinyl alcohol, polyvinyl acetate, partially acetylated or partially acetalized polyvinyl alcohol, and copolymers of vinyl alcohol, vinyl butyral, and vinyl acetate. Specific examples of vinyl alcohol polymers include the "S-LEC (registered trademark) B" series, the "S-LEC (registered trademark) K (KS)" series, the "S-LEC (registered trademark) SV" series (all manufactured by Sekisui Chemical Co., Ltd.) and the "MOWITAL (registered trademark)" series (manufactured by Kuraray Co., Ltd.). Examples of acrylic polymers include polyacrylic acid, sodium polyacrylate, acrylic acid / maleic acid copolymer sodium salt, acrylic acid / sulfonic acid monomer copolymer sodium salt and other polyacrylic acid salts, polyacrylates such as polymethyl acrylate and polyethyl acrylate, poly-α-haloacrylate, poly-α-cyanoacrylate, and polyacrylamide.
[0027] Examples of the polysaccharides include glycogen, amylose, agarose, pullulan, cellulose, dextrin, dextran, fructan, chitin, xanthan gum, guar gum, casein, gum arabic, gelatin, agar, arabinan, curdlan, callose, carboxymethyl starch, chitosan, quince seed, glucomannan, gellan gum, tamarind gum, dextran, niger polysaccharide, hyaluronic acid, pustules, haran, pectin, laver polysaccharide, laminarin, lichen polysaccharide, carrageenan, alginic acid, tragacanth gum, alkali gum, and locust bean gum. Among them, nonionic polysaccharides are preferred, and glycogen, amylose, agarose, pullulan, cellulose, dextrin, dextran, fructan, and chitin are preferred, and cellulose is more preferred.
[0028] Examples of the cellulose include cellulose ethers such as alkyl cellulose, carboxyalkyl cellulose, hydroxyalkyl cellulose, and hydroxyalkyl alkyl cellulose. Examples of the alkyl cellulose include methyl cellulose and ethyl cellulose. Examples of the carboxyalkyl cellulose include carboxymethyl cellulose and the like. Examples of the hydroxyalkyl cellulose include hydroxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose. Examples of the hydroxyalkyl alkyl cellulose include hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl ethyl cellulose, and hydroxyethyl ethyl methyl cellulose. Among them, hydroxyalkyl cellulose or hydroxyalkyl alkyl cellulose is preferred, hydroxyalkyl cellulose is more preferred, and hydroxyethyl cellulose is further preferred.
[0029] The weight average molecular weight of the cellulose ether is preferably 1000 to 10000. The weight average molecular weight can be measured, for example, by gel permeation chromatography (GPC) using a differential refractive index detector. Specific examples of cellulose ether include "SUNROSE (registered trademark)" series (produced by Nippon Paper Industries, Ltd.), "METOLOSE (registered trademark)" series (produced by Shin-Etsu Chemical Co., Ltd.), and "HEC CF grade" (produced by Sumitomo Seika Chemicals, Ltd.).
[0030] When the dispersion obtained by the present method contains a viscosity modifier, at least one selected from the group consisting of acrylic polymers, vinyl alcohol polymers and cellulose is preferred. The average molecular weight of the viscosity modifier is preferably 3000 or more, more preferably 10000 or more, further preferably 100000 or more, and particularly preferably 300000 or more. The average molecular weight of the viscosity modifier is preferably 1000000 or less, more preferably 500000 or less. In this case, the dispersion obtained by this method is likely to be excellent in physical properties such as dispersion stability.
[0031] The viscosity modifier is preferably water soluble. The thermal decomposition temperature of the viscosity modifier is preferably 150°C or higher, more preferably 200°C or higher. The thermal decomposition temperature of the viscosity modifier is preferably 320°C or lower, more preferably 300°C or lower. The thermal decomposition temperature is preferably below the melting temperature of the F polymer. In this case, the viscosity modifier is likely to function well as a binder, and the viscosity modifier is unlikely to remain in the molded product formed from the dispersion obtained by this method, and the physical properties of the molded product, such as electrical properties, are likely to be excellent.
[0032] When a viscosity modifier is contained, its content is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, relative to the total mass of the liquid composition. The content of the viscosity modifier is preferably 30% by mass or less, more preferably 10% by mass or less, relative to the total mass of the liquid composition. The content ratio of the viscosity modifier to the content of the F particles in the liquid composition is preferably 0.001 or more, more preferably 0.003 or more. The content ratio is preferably 0.05 or less, more preferably 0.03 or less, and further preferably 0.01 or less.
[0033] In this method, the liquid composition may further contain a water-soluble solvent having a surface tension of 20 to 30 mN / m. As the water-soluble solvent having a surface tension of 20 to 30 mN / m, it is a compound that is liquid at atmospheric pressure and 25°C, preferably a compound having a boiling point of 160°C or less, and more preferably a compound having a boiling point of 120°C or less. Such a water-soluble solvent preferably forms an azeotrope with water. In addition, in this specification, a water-soluble solvent refers to a solvent having a solubility in water of 100 g / L or more. The water-soluble solvent may be used alone or in combination of two or more. When two water-soluble solvents are used, the two water-soluble solvents are preferably compatible with each other. As the water-soluble solvent, monohydric alcohols having 1 to 6 carbon atoms are preferred, and methanol (23 mN / m), ethanol (23 mN / m), 1-propanol (24 mN / m), 2-propanol (22 mN / m), 1-butanol (25 mN / m), 2-butanol (24 mN / m), isobutanol (23 mN / m), 1-methoxy-2-propanol (26 mN / m), 2-propoxy-ethanol (27 mN / m), 1-propoxy-2-propanol (25 mN / m), and 2-ethoxyethanol (26 mN / m) are more preferred, and ethanol is further preferred. The numerical values in parentheses are the surface tensions of the monohydric alcohols.
[0034] In this method, a wet bead mill is used to grind liquid with a density of 1.15 to 1.5 g / cm 3 The liquid composition containing the F particles and the liquid dispersion medium is treated to obtain a dispersion containing the F particles. The liquid composition is preferably prepared by mixing the powder of the F polymer with a liquid dispersion medium. Here, the powder of the F polymer refers to an aggregate of F particles, which may be an aggregate of the F particles themselves or an aggregate of a part of the F particles agglomerated. When preparing the liquid composition, the F particles and the liquid dispersion medium may be mixed once or in multiple batches. In addition, when the above-mentioned surfactant, viscosity modifier, and water-soluble solvent are further mixed in the liquid composition as needed, the F particles and the liquid dispersion medium may be mixed at once, the components may be added sequentially and then mixed, or a mixture in which the components are dissolved or dispersed in the liquid dispersion medium may be added to the mixture of the F particles and the liquid dispersion medium and then mixed.
[0035] Examples of mixing devices for preparing liquid compositions include stirring devices equipped with blades such as Henschel mixers, pressure kneaders, Banbury mixers, and planetary mixers, and dispersing devices equipped with other mechanisms such as microfluidizers, nanofluidizers, Ultimaizer dispersers, ultrasonic homogenizers, dissolvers, dispersers, high-speed impeller dispersers, thin-film gyratory high-speed mixers, auto-rotational-revolution stirrers, and V-type mixers.
[0036] In the preparation of the liquid composition, after the above mixing, it is preferred to perform a degassing treatment. Examples of such degassing treatments include a standing treatment, a reduced pressure treatment, a hot air treatment, etc. These may be combined to perform the degassing treatment. Specifically, in the preparation of the liquid composition, it is preferred to perform a mixing treatment using the above-mentioned stirring device or dispersing device and further perform a degassing treatment by a reduced pressure treatment (reduced pressure degassing treatment).
[0037] In this method, the liquid density of the liquid composition is 1.15 to 1.5 g / cm 3 , preferably 1.24 to 1.42 g / cm 3 , more preferably 1.28 to 1.38 g / cm 3 If the liquid density of the liquid composition is within the above range, the above mechanism of action is likely to be highly manifested. In particular, when the liquid dispersion medium in the liquid composition is a liquid dispersion medium with water as the main component, specifically when the proportion of water in the liquid dispersion medium is 80 to 100% by mass, the above mechanism of action is likely to be highly manifested. The liquid density of the liquid composition can be adjusted by adjusting the types or amounts of the components contained in the liquid composition or by the above-mentioned static treatment, reduced pressure treatment, hot air treatment, etc. Specific means for adjusting the liquid density of the liquid composition include means for adjusting the content of the F particles in the liquid composition, more specifically, means for adjusting the content to more than 30% by mass.
[0038] In this method, the viscosity of the liquid composition is preferably 100 to 10000 mPa·s, more preferably 500 to 3000 mPa·s, and further preferably 1000 to 5000 mPa·s. In this case, the above-mentioned mechanism of action is more likely to be highly manifested. The viscosity of the liquid composition is preferably adjusted by the type of components contained in the liquid composition, in particular by using the above-mentioned viscosity modifier.
[0039] In this method, the surface tension of the liquid composition is preferably 15 to 45 mN / m, more preferably 20 to 35 mN / m, and further preferably 20 to 30 mN / m. In this case, the above-mentioned mechanism of action is more likely to be highly manifested. The surface tension of the liquid composition is preferably adjusted by the type of components contained in the liquid composition, especially by using the above-mentioned water-soluble solvent.
[0040] The bead mill used in this method comprises, for example, a hollow cylindrical container filled with grinding beads as a medium, and a stirrer arranged in the container to stir the liquid composition and the grinding beads. As the stirrer, for example, a hollow cylindrical or impeller-shaped stirrer arranged coaxially with the container can be used. Bead mills are classified into batch type, through type and circulation type according to their operation modes. The treatment (dispersion treatment) of this method uses beads with a diameter of 2 mm or less, and is preferably selected from any of batch type, through type or circulation type bead mills. For example, the treatment of a circulating bead mill is to transport the liquid composition from a tank to a bead mill, treat it at the bead mill, and then separate it from the beads by a bead separation means and return it to the tank, repeating until the desired dispersion is obtained. As the bead separation means, centrifugal separation devices, GAP separators, separation sieves, etc. can be cited. In addition, the container can be cooled for treatment as needed. Furthermore, after the bead mill treatment, a static treatment, a reduced pressure treatment, a hot air treatment, etc. may be further performed. Specifically, it is preferred to further perform a reduced pressure degassing treatment.
[0041] The diameter of the grinding beads is preferably in the range of 0.1 to 10 mm, more preferably in the range of 1 to 5 mm. The material of the grinding beads is not particularly limited, and examples thereof include zirconium oxide, silicon oxide, aluminum oxide, glass, and metal. Examples of the bead mill include the vertical "Alpha Mill" manufactured by AIMEX Co., Ltd., the horizontal "New Visco Mill NVM" and "Ultra Visco Mill UVM", the "DYNO-MILL" manufactured by WAB, the "Ultra Apex Mill" manufactured by Hiroshima Metal & Machinery Co., Ltd., the "My Mill" manufactured by Nippon Coking Industry Co., Ltd., and the "Star Mill" manufactured by Ashizawa Finetech Co., Ltd.
[0042] In the present method, the dispersion after the wet bead mill treatment may be further mixed with at least one of a liquid dispersion medium, an aromatic polymer, or an inorganic filler. The types of the liquid dispersion medium that may be further mixed are the same as those of the above-mentioned liquid dispersion medium.
[0043] When the dispersion obtained by this method further contains an inorganic filler, a molded product such as a coating film (polymer layer) formed from the dispersion tends to be excellent in electrical properties and low linear expansion properties. The shape of the inorganic filler can be any of spherical, needle-shaped (fibrous), and plate-shaped. Specifically, it can be spherical, flaky, layered, leaf-shaped, almond-shaped, columnar, cockscomb-shaped, equiaxed, leaf-shaped, mica-shaped, blocky, flat, wedge-shaped, rosette-shaped, mesh-shaped, and prism-shaped. Examples of the inorganic filler include silicon compounds such as quartz powder, silicon dioxide, wollastonite, talc, silicon nitride, silicon carbide, and mica; nitrogen compounds such as boron nitride and aluminum nitride; metal oxides such as aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide; carbon fibers; allotropes of carbon such as graphite, graphene, and carbon nanotubes; and metals such as silver and copper. The inorganic filler may be used alone or in combination of two or more. The D50 of the inorganic filler is preferably 0.1 to 50 μm. The surface of the inorganic filler may be surface treated with a silane coupling agent.
[0044] Specific examples of suitable inorganic fillers include silica fillers ("admafin (registered trademark)" series (produced by Yaduma Technology Co., Ltd.), "SFP (registered trademark)" series (produced by Denka Co., Ltd.), "E-SPHERES" series (produced by Pacific Cement Co., Ltd.)), zinc oxide fillers ("FINEX (registered trademark)" series (produced by Sakai Chemical Industry Co., Ltd.)), titanium oxide fillers ("TIPAQUE (registered trademark)" series (produced by Nissan)), and the like. series (produced by Ishihara Sangyo Co., Ltd.), "JMT (registered trademark)" series (produced by Teika Co., Ltd.), talc fillers ("SG" series (produced by Nippon Talc Co., Ltd.)), block talc fillers ("BST" series (produced by Nippon Talc Co., Ltd.)), boron nitride fillers ("UP40MF" series, "UP40" series (both produced by JFE Mining Co., Ltd.), "UHP" series (produced by Showa Denko K.K.), "Denka Boron Nitride" series of "GP", "HGP" grades (produced by Denka Co., Ltd.)), etc.). When the dispersion obtained by this method contains an inorganic filler, the content thereof is preferably 1 to 25% by mass based on the dispersion.
[0045] If the dispersion obtained by this method further contains an aromatic polymer, it is preferred from the viewpoint of further improving the dispersion stability of the particles F. Such an aromatic polymer may be contained in the form of non-hollow particles, or may be dissolved or dispersed in the liquid dispersion medium. Examples of the aromatic polymer include polyester resins such as liquid crystalline aromatic polyesters, polyimide resins, polyamideimide resins, epoxy resins, maleimide resins, polyurethane resins, polyphenylene ether resins, polyphenylene ether resins, and polyphenylene sulfide resins. Among them, at least one aromatic imide polymer selected from aromatic polyimide, aromatic polyamic acid, aromatic polyamideimide, and aromatic polyamideimide precursors is more preferred. The aromatic polymer is preferably contained in the form of a varnish dissolved in a liquid dispersion medium.
[0046] Specific examples of aromatic imide polymers include the "UPIA-AT" series (manufactured by UBE Corporation), the "Neopulim (registered trademark)" series (manufactured by Mitsubishi Gas Chemical Co., Ltd.), the "SPIXAREA (registered trademark)" series (manufactured by Somaron Corporation), the "Q-PILON (registered trademark)" series (manufactured by PI Technology Laboratory), the "WINGO" series (manufactured by WINGO Technology Co., Ltd.), the "Tohmide (registered trademark)" series (manufactured by DICK TOKA CO., LTD.), the "KPI-MX" series (manufactured by Kawamura Sangyo Co., Ltd.), and "HPC-1000" and "HPC-2100D" (both manufactured by Showa Denko Materials Co., Ltd.). When the dispersion obtained by this method further contains an aromatic polymer, the content of the aromatic polymer relative to the F particles is preferably 1 to 25% by mass.
[0047] The dispersion obtained by this method may be further added with various additives such as thixotropy imparting agent, defoaming agent, dehydrating agent, plasticizer, weathering agent, antioxidant, heat stabilizer, lubricant, antistatic agent, whitening agent, colorant, conductive agent, release agent, flame retardant, etc.
[0048] The present invention provides a dispersion liquid (hereinafter also referred to as "the present dispersion liquid") comprising F particles and a liquid dispersion medium, which is obtained by wet bead milling and has a particle concentration of less than 1000 particles / ml with a particle size of 60 μm or more as measured by a particle counter. From the viewpoint that the surface of a molded product such as a layer formed from the present dispersion is less likely to have streaks, cracks or defects, the concentration of particles having a particle size of 60 μm or more in the present dispersion as measured by a particle counter is preferably less than 500 particles / ml, more preferably less than 200 particles / ml. In addition, the lower limit is preferably 1 particle / ml. The details of the F polymer, F particles and liquid dispersion medium in the present dispersion are the same as those described above in the description of the present method.
[0049] The present dispersion is preferably prepared by this method. Specifically, the present dispersion is preferably processed by a wet bead mill to a liquid density of 1.15 to 1.5 g / cm 3The liquid composition comprising F particles and a liquid dispersion medium is obtained. The dispersion stability and operability of this dispersion are excellent. In addition, the formed products such as the coating (polymer layer) formed by this dispersion have excellent properties such as heat resistance, electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) brought by the F polymer, and particularly excellent surface appearance.
[0050] The content of F particles in the present dispersion is preferably greater than 30% by mass, more preferably greater than 35% by mass, from the viewpoint of being easy to form a thick layered molded product therefrom and being easy to impart high physical properties to the F polymer in the obtained molded product. The content of F particles is preferably less than 75% by mass, more preferably less than 60% by mass. The content of the tetrafluoroethylene polymer particles is preferably greater than 30% by mass and less than 75% by mass, and more preferably greater than or equal to 35% by mass and less than or equal to 60% by mass. The content of the liquid dispersion medium in the present dispersion is preferably 25% by mass or more, more preferably 40% by mass. The content of the liquid dispersion medium is preferably less than 70% by mass, more preferably less than 65% by mass. In addition, the content of the liquid dispersion medium in the present dispersion is preferably 60 to 180% by mass relative to the content of the F particles.
[0051] The present dispersion may contain surfactants, viscosity modifiers, water-soluble solvents, aromatic polymers, inorganic fillers, and various additives as required. The details of the surfactants, viscosity modifiers, water-soluble solvents, aromatic polymers, inorganic fillers, and various additives are the same as those described above.
[0052] When the present dispersion contains the surfactant, its content is preferably 1 to 15 parts by mass, more preferably 3 to 10 parts by mass, relative to 100 parts by mass of the F particles. In addition, when the present dispersion contains the surfactant, its content is preferably 1 to 10% by mass relative to the content of the F particles.
[0053] When the present dispersion contains the water-soluble solvent, its content is preferably 0.1% by mass or more, more preferably 1% by mass or more. The content of the water-soluble solvent is preferably 10% by mass or less, more preferably 5% by mass or less. In addition, when the present dispersion contains the water-soluble solvent, its content is preferably 1 to 10% by mass relative to the content of the F particles. It is believed that this water-soluble solvent also plays the role of a defoamer such as a foam suppression effect or a bubble breaking effect.
[0054] The viscosity of the present dispersion is preferably 10 mPa·s or more, more preferably 100 mPa·s or more. The viscosity of the present dispersion is preferably 10000 mPa·s or less, more preferably 3000 mPa·s or less. In this case, the present dispersion has excellent coating properties and is easy to form a molded product such as a coating film (polymer layer) with any thickness. In addition, in the molded product obtained from the present dispersion within the viscosity range of this range, the physical properties of the F polymer are easily highly presented. The thixotropic ratio of the present dispersion is preferably 1.0 to 3.0. In this case, the present dispersion has excellent coating properties and uniformity, and a denser molded product can be easily produced. These liquid physical properties are easily improved when the present dispersion contains the above-mentioned viscosity modifier.
[0055] When the liquid dispersion medium of the present method is water, from the viewpoint of improving long-term storage properties, the pH of the dispersion is more preferably 8 to 10. The pH of such a dispersion can be adjusted by a pH adjuster (amine, ammonia, citric acid, etc.) or a pH buffer (tris(hydroxymethyl)aminomethane, ethylenediaminetetraacetic acid, ammonium bicarbonate, ammonium carbonate, ammonium acetate, etc.).
[0056] The dielectric constant of the molded product formed by the dispersion obtained by this method is preferably less than 2.4, more preferably less than 2.0. In addition, the dielectric constant is preferably greater than 1.0. The dielectric loss tangent of the molded product is preferably less than 0.0022, more preferably less than 0.0020. In addition, the dielectric loss tangent is preferably greater than 0.0010. The thermal conductivity of the molded product is preferably greater than 1 W / m·K, more preferably greater than 3 W / m·K.
[0057] If the dispersion obtained by this method is subjected to a forming method such as extrusion into a sheet, a formed product such as a sheet containing the F polymer can be formed. The extruded sheet can be further cast by pressure forming, calendaring, etc. The sheet is preferably further heated to remove the liquid dispersion medium and calender the F polymer.
[0058] The thickness of the sheet formed from the dispersion obtained by this method is preferably 1 to 1000 μm. The suitable ranges of the dielectric constant, dielectric loss tangent and thermal conductivity of the sheet are respectively the same as those of the above-mentioned molded product. In addition, the thermal conductivity of the sheet refers to the thermal conductivity in the in-plane direction of the sheet. The linear expansion coefficient of the sheet is preferably 100 ppm / °C or less, more preferably 80 ppm / °C or less. The lower limit of the linear expansion coefficient of the sheet is preferably 30 ppm / °C. In addition, the linear expansion coefficient is a value obtained by measuring the linear expansion coefficient of the test piece in the range of 25°C to 260°C according to the measurement method specified in JIS C6471:1995.
[0059] When such a sheet is laminated on a substrate, a laminate can be formed. Examples of a method for producing the laminate include a method of extruding the dispersion obtained by the present method onto the substrate, and a method of thermocompression bonding the sheet and the substrate. As the substrate, for example, there can be listed: metal substrates such as metal foils of copper, nickel, aluminum, titanium, and alloys thereof; films of heat-resistant resins such as polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyallyl ether ketone, polyamideimide, liquid crystalline polyester, and tetrafluoroethylene polymers; prepreg substrates (precursor of fiber-reinforced resin substrates), ceramic substrates such as silicon carbide, aluminum nitride, and silicon nitride; glass substrates, etc.
[0060] Examples of the shape of the substrate include a flat surface, a curved surface, and a concave-convex shape. The substrate may be in any of a foil, a plate, a film, and a fiber. The ten-point average roughness of the substrate surface is preferably 0.01 to 0.05 μm. The substrate surface can be surface treated with a silane coupling agent or plasma treated. As such silane coupling agents, preferably silane coupling agents with functional groups such as 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-isocyanatepropyltriethoxysilane. The peel strength between the sheet and the substrate is preferably 10 to 100 N / cm or more.
[0061] Among them, as a base material forming a laminate, a polyimide film is preferable. The dielectric constant of the polyimide film at 5.8 GHz is preferably 3.5 or less, and more preferably 3.4 or less. In addition, the dielectric loss tangent of the polyimide film at 5.8 GHz is preferably 0.006 or less, and more preferably 0.0055 or less. The dielectric constant and dielectric loss tangent can be measured, for example, using a perturbation dielectric constant measuring apparatus CP521 (for 5.8 GHz) manufactured by Agilent Technologies Inc. / Kanto Denshi Applied Development Co., Ltd. connected to a network analyzer 8722A / C / D.
[0062] The water absorption of the polyimide film is preferably 1.2% or less, more preferably 1.1% or less. The water absorption is obtained by, for example, cutting the polyimide film into a circle with a diameter of 6 cm, measuring the mass after heat treatment at 200°C for 1 hour (mass when dry: W0), then leaving it to stand in distilled water for 1 day to allow it to absorb water, and measuring the mass of the film after water absorption (W1), and calculating it using the following calculation formula. Water absorption (%) = (W1-W0) / W0×100
[0063] The linear expansion coefficient of the polyimide film at 50 to 200°C is preferably 2 to 18 ppm / °C, more preferably 4 to 16 ppm / °C. The linear expansion coefficient can be measured, for example, by using a thermomechanical analyzer such as TMA-50 manufactured by Shimadzu Corporation in a measurement temperature range of 50 to 200°C at a temperature increase condition of 10°C / minute. Specifically, under a load of 0.25N, the temperature is first increased from 35°C to 230°C at 10°C / minute, then maintained at the same temperature for 5 minutes, then cooled to 35°C at 10°C / minute and maintained at the same temperature for 30 minutes, and then heated to 230°C at 10°C / minute again, and the data of 50 to 200°C at the second temperature increase are averaged to calculate the linear expansion coefficient.
[0064] The storage modulus of the polyimide film at 360° C. is preferably 0.1 GPa or more, more preferably 0.15 GPa or more. The storage modulus is measured, for example, using a viscoelasticity device such as DMS EXSTER6100 manufactured by Hitachi High-Technologies in a temperature range of 25 to 400° C. at a heating rate of 2° C. / min, a frequency of 5 Hz, and a nitrogen atmosphere, and the value at 360° C. is recorded as the 360° C. storage modulus.
[0065] The polyimide film as the substrate preferably has a high yield strength. Specifically, the polyimide film preferably has a stress at 5% strain of 180 MPa or more, more preferably 210 MPa or more. The above stress at 5% strain is preferably 500 MPa or less. The polyimide film as the substrate preferably has difficulty in plastic deformation. Specifically, the stress at 15% strain of the polyimide film is preferably 225 MPa or more, more preferably 245 MPa or more. The stress at 15% strain is preferably 580 MPa or less. When the polyimide film has high yield strength, and in particular, is difficult to deform plastically, the absolute value of the linear expansion coefficient of the laminate is likely to be sufficiently low, and the occurrence of warping can be more reliably prevented.
[0066] The tensile modulus of the polyimide film is preferably 5 GPa or more, more preferably 6 GPa or more. The elongation at break of the polyimide film is preferably 20% or more, more preferably 30% or more. The tensile modulus of elasticity and elongation at break of the polyimide film can be measured, for example, using RTM-250 (Aiande Co., Ltd.) under the conditions of sample width: 10 mm, grid spacing: 50 mm, and tensile speed: 100 mm / min. In this case, even if the laminate is heated and cooled during its processing, its operability is still excellent. That is, if the tensile elastic modulus of polyimide film is above the above-mentioned lower limit, then during the heating and cooling during processing, the shrinkage of the polymer layer is effectively alleviated due to the elasticity of the polyimide film, and the laminate is not easy to wrinkle, and the physical property (surface smoothness, etc.) of the processed product obtained is easily improved. This tendency is particularly obvious in the case where the F polymer content or the thickness of the polymer layer in the polymer layer is large. In addition, if the tensile elastic modulus of polyimide film is below the above-mentioned upper limit, the flexibility of the laminate is easily further improved.
[0067] The aromatic polyimide is a polyimide containing an aromatic group in the repeating unit structure, and examples thereof include aromatic polyimides obtained by synthesizing a polyamic acid by reacting a diamine with a carboxylic dianhydride and imidizing the polyamic acid by a thermal imidization method or a chemical imidization method. Examples of the solvent used for synthesizing the polyamic acid include N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.
[0068] Examples of the diamine include 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl propane, 4,4'-diaminodiphenyl methane, 4,4'-oxydiphenylamine, 3,3'-oxydiphenylamine, 3,4'-oxydiphenylamine, 4,4'-diaminodiphenyl diethylsilane, 4,4'-diaminodiphenyl silane, 1,4-diaminobenzene (p-phenylenediamine), 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4 ...3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)biphenyl, 1,4-bis(3-aminophenoxy)biphenyl, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)biphenyl, 1,4-bis(3-aminophenoxy)biphenyl, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)biphenyl, 1,4 (4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 3,3'-dihydroxy-4,4'-diamino-1,1'-biphenyl, 2,4-diaminotoluene, 2'-methoxy-4,4'-diaminobenzanilide, 4,4'-diaminobenzanilide. These diamine components may be used alone or in combination of two or more.
[0069] Examples of the carboxylic acid dianhydride include pyromellitic acid dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 2,2',3,3'-biphenyltetracarboxylic acid dianhydride, 2,3,3',4'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic acid dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3,2',3'-benzophenonetetracarboxylic dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenyl)-1,1,3,3-tetramethyldicyclohexane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride. These carboxylic dianhydride components may be used alone or in combination of two or more.
[0070] Furthermore, when the present dispersion is placed on the surface of a substrate and heated to form a polymer layer containing F polymer (hereinafter also referred to as "F layer"), a laminate having a substrate layer composed of a substrate and the F layer in this order can be obtained. Preferably, the present dispersion is placed on the surface of the substrate, heated to remove the liquid dispersion medium, and further heated to calcine the F polymer to form the F layer. When the substrate is separated from the laminate, a sheet containing the F polymer can be obtained. Examples of the substrate include the same substrates as those which can be laminated on the above-mentioned sheet, and the preferred embodiments thereof are also the same.
[0071] Examples of a method for preparing the present dispersion include a coating method, a droplet spraying method, and a dipping method, and a roll coating method, a doctor blade coating method, a bar coating method, a die coating method, or a spray coating method is preferred. The heating for removing the liquid dispersion medium is preferably carried out at 100 to 200° C. for 0.1 to 30 minutes. During the heating at this time, the liquid dispersion medium does not need to be completely removed, as long as it is removed to the extent that the layer formed by the accumulation of F particles can maintain a self-supporting film. In addition, air can be blown during heating to promote the removal of the liquid dispersion medium by air drying.
[0072] The heating for calcining the F polymer is preferably performed at a temperature equal to or higher than the calcining temperature of the F polymer, more preferably at 360 to 400° C. for 0.1 to 30 minutes. Examples of the heating device in each heating process include an oven and a ventilation drying furnace. The heat source in the device may be a contact heat source (hot air, a heating plate, etc.) or a non-contact heat source (infrared rays, etc.). In addition, each heating may be performed under normal pressure or under reduced pressure. In addition, the atmosphere during each heating may be any of an air atmosphere and an inert gas (helium, neon, argon, nitrogen, etc.) atmosphere.
[0073] The F layer is formed by the configuration and heating steps of the present dispersion. These steps may be performed once or repeated twice or more. For example, the present dispersion may be configured on the surface of the substrate and heated to form the F layer, and the present dispersion may be further configured on the surface of the F layer and heated to form the second F layer. The present dispersion may also be further configured on the surface of the substrate and heated to remove the liquid dispersion medium in the stage of removing the liquid dispersion medium. The present dispersion can be disposed on only one surface of the substrate or on both surfaces of the substrate. In the former case, a laminate having a substrate layer and an F layer on a single surface of the substrate layer can be obtained, and in the latter case, a laminate having a substrate layer and F layers on both surfaces of the substrate layer can be obtained.
[0074] Specific suitable examples of the laminate include a metal-clad laminate having a metal foil and an F layer on at least one surface of the metal foil, and a multilayer film having a polyimide film and F layers on both surfaces of the polyimide film. The suitable ranges of the dielectric constant, dielectric loss tangent, thermal conductivity, linear expansion coefficient, and peel strength between the F layer and the substrate layer are the same as the suitable ranges of the dielectric constant, dielectric loss tangent, thermal conductivity, linear expansion coefficient, and peel strength between the sheet formed from the above-mentioned dispersion and the substrate.
[0075] The present invention is a laminate (hereinafter also referred to as "the present laminate") in which F layers are formed on both surfaces of a substrate and which includes the F layer, a substrate layer composed of the substrate, and the F layer in this order. In the present laminate, from the viewpoint of excellent water absorption and electrical properties, the substrate is preferably a polyimide film, which contains at least two diamine units derived from 1,4-bis(4-aminophenoxy)benzene and 4,4'-diaminobenzanilide, has a dielectric constant of less than 3.5 at 5.8 GHz, a dielectric loss tangent of less than 0.006, a water absorption of less than 1.2%, and a linear expansion coefficient of 2 to 18 ppm / °C at 50 to 200°C. Furthermore, the thickness of the polyimide film is preferably 10 to 50 μm or less.
[0076] The thickness of the F layer varies depending on the purpose of the present laminate, but is preferably in the range of 10 to 200 μm. In addition, the thickness of the F layer is preferably at least 0.1 times the thickness of the polyimide film substrate, and the ratio of the thickness of the substrate to the total thickness of the F layer is preferably 90 / 10 to 10 / 90. In addition, when the substrate is the above-mentioned polyimide film, a primer layer may be further included between the F layer and the above-mentioned polyimide film.
[0077] The dispersion obtained by this method and the present dispersion can be used as a material for imparting insulation, heat resistance, corrosion resistance, chemical resistance, water resistance, impact resistance, and thermal conductivity. Specifically, the dispersion obtained by this method and the present dispersion can be used for printed wiring boards, thermal interface materials, substrates for power modules, coils used in power devices such as motors, vehicle engines, heat exchangers, vials, syringes (syringes), ampoules, medical wires, secondary batteries such as lithium ion batteries, primary batteries such as lithium batteries, free radical batteries, solar cells, fuel cells, lithium ion capacitors, hybrid capacitors, capacitors, capacitors (aluminum electrolytic capacitors, tantalum electrolytic capacitors, etc.), electrochromic elements, electrochemical conversion elements, electrode adhesives, electrode diaphragms, electrodes (positive and negative electrodes). In addition, the dispersion obtained by this method and the present dispersion can also be used as an adhesive for bonding parts. Specifically, the dispersion obtained by this method and the present dispersion can be used for bonding ceramic parts, bonding metal parts, bonding IC chips or resistors, capacitors and other electronic parts on the substrate of semiconductor elements or module parts, bonding circuit substrates and heat sinks, and bonding LED chips on substrates.
[0078] The dispersion obtained by this method, the shaped products such as sheets formed from this dispersion, and the laminated body including this laminated body can be used as antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, heat dissipation parts, etc. Specifically, it can be used as wire coating materials (wires for aircraft, rectangular wires, FFC (Flexible flat cable), etc.), enameled wire coating materials used in motors of electric vehicles, etc., power generation coating materials, electrical insulating tapes, insulating tapes for oil drilling, oil pipelines, hydrogen tanks, printed circuit board materials, separation membranes (precision filtration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode adhesives (for lithium secondary batteries, fuel cells, etc.), fuel cell carrier membranes, tape substrate films for semiconductor manufacturing processes (dicing tapes, pick-up tapes, etc.), semiconductor molding release films, liquid crystal antennas, reflectors, transmission lines, COF (chip on film) film), electrostatic chucks for semiconductor manufacturing processes, electrostatic chucks for display manufacturing processes, copy rollers, covers for furniture, automobile dashboards, home appliances, etc., sliding parts (load bearings, yaw bearings, sliding shafts, valves, bearings, bushings, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, food conveyor belts), tension ropes, wear pads, wear strips, tube lights, test sockets, wafer guides, wear parts of centrifugal pumps, chemical and water supply pumps, tools (shovels, files, chisels, saws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, racket strings, molds, toilets, container covering materials, heat dissipation substrates for power devices, heat dissipation components for wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOS FET, CPU, heat sink, metal heat sink, blades of windmills, wind power generation equipment or aircraft, computer or display housing, electronic device materials, automobile interior and exterior, processing machines or vacuum furnaces that perform heat treatment under low oxygen, sealing materials for plasma processing equipment, heat dissipation parts in processing units such as sputtering or various dry etching equipment, and electromagnetic wave shielding bodies.
[0079] The dispersion obtained by this method, the shaped product such as a sheet formed from the dispersion, and the laminate including the laminate can be used as electronic substrate materials such as flexible printed circuit boards and rigid printed circuit boards, protective films, or heat dissipation substrates, especially heat dissipation substrates for automobiles. Example
[0080] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited thereto. 1. Preparation of Ingredients [F polymer] F particles 1: each containing 97.9 mol%, 0.1 mol%, and 2.0 mol% of TFE units, NAH units, and PPVE units, respectively. 6Particles of tetrafluoroethylene polymer (melting temperature: 300°C) with 1000 carbonyl groups in the main chain (D50: 2.0 μm, specific surface area: 7 m 2 / g) [Surfactant] Surfactant 1: Nonionic silicone surfactant having a polysiloxane chain on the main chain and a polyoxyethylene group on the side chain [Viscosity modifier] Viscosity modifier 1: Hydroxyethyl cellulose (degree of substitution 2.4) [Water-soluble solvent] Ethanol (surface tension 23mN / m)
[0081] 2. Preparation Example of Dispersion Liquid [Example 1] F particles 1, surfactant 1, and water were mixed to prepare a liquid composition 1 containing 45% by mass of F particles 1. During the preparation, viscosity modifier 1 and ethanol were added respectively, and the mixture was treated at 1000 rpm for 20 minutes using a high-speed dispersing mixer ("Hyper HSPV10" manufactured by Ashizawa Fine Technology Co., Ltd.), and further deaerated under reduced pressure using a deaerator ("Bubble Buster 400" manufactured by Ashizawa Fine Technology Co., Ltd.) at a frequency of 40 Hz and a vacuum degree of -0.1 MPaG. 1.44 ml of the liquid composition 1 was extracted and diluted 250 times, and the whole amount was passed through a particle counter, i.e., a particle size distribution measuring device ("AccuSizer (registered trademark) A7000APS" manufactured by Entegris Corporation of Japan, using LE400 sensor) to measure the number of coarse particles with a particle size of 60 μm or more (particle concentration), which was 4000 particles / ml. In addition, the liquid density, surface tension and viscosity of the liquid composition 1 were 1.32 g / cm 3 , 24mN / m, 3000mPa·s.
[0082] Thereafter, the liquid composition 1 was added to a wet bead mill device having a zirconia bead diameter of 0.3 mm ("MugenFlow 10" manufactured by Ashizawa Mei-Tech Co., Ltd.), and the bead mill treatment was performed under the conditions of a bead filling rate of 85%, a mill peripheral speed of 7 m / s, a liquid flow rate of 4.0 L / min, a residence time of 1.10 min, and a number of passes of 4 times, and the obtained treated product was further subjected to a reduced pressure degassing treatment using a deaerator ("Bubble Buster 400" manufactured by Ashizawa Mei-Tech Co., Ltd.) under the conditions of a frequency of 40 Hz and a vacuum degree of -0.1 MPaG to obtain a dispersion 1. The dispersion 1 had a good dispersed flow state, and the number of coarse particles (particle concentration) thereof was measured in the same manner as above, and was 100 particles / ml.
[0083] [Example 2] The F particles 1, the surfactant 1, and water were mixed in the same manner as in Example 1 to prepare a liquid composition 2 containing 45% by mass of the F particles 1. The number of coarse particles of the liquid composition 2 was measured in the same manner as in Example 1 and was 6000 particles / ml. The liquid density, surface tension, and viscosity of the liquid composition 2 were 1.34 g / cm 3 , 33 mN / m, 3000 mPa·s. The bead mill treatment and the subsequent reduced pressure degassing treatment were carried out in the same manner as in Example 1 except that the liquid composition 2 was used to obtain a dispersion 2. The number of coarse particles (particle concentration) of the dispersion 2 was 800 particles / ml. [Example 3] The F particles 1, surfactant 1, and water were mixed in the same manner as in Example 1, except that only ethanol was added during the preparation, to prepare a liquid composition 3 containing 45% by mass of the F particles 1. The number of coarse particles in the liquid composition 3 was 4000 particles / ml, and the liquid density, surface tension, and viscosity were 1.33 g / cm 3 , 25 mN / m, 900 mPa·s. The bead mill treatment and the subsequent reduced pressure degassing treatment were carried out in the same manner as in Example 1 except that the liquid composition 3 was used to obtain a dispersion 3. The number of coarse particles (particle concentration) of the dispersion 3 was 900 particles / ml.
[0084] [Example 4] Except for changing the content of F particles 1, F particles 1, surfactant 1, and water were mixed in the same manner as in Example 1 to prepare a liquid composition 4 containing 25% by mass of F particles 1. In addition, viscosity modifier 1 and ethanol were added during preparation. The number of coarse particles in liquid composition 4 was 3000 / ml, and the liquid density, surface tension, and viscosity of liquid composition 4 were 1.17 g / cm 3 , 24 mN / m, 2500 mPa·s. The bead mill treatment and the subsequent reduced pressure degassing treatment were carried out in the same manner as in Example 1 except that the liquid composition 4 was used to obtain a dispersion 4. The number of coarse particles (particle concentration) of the dispersion 4 was 3000 particles / ml.
[0085] Each dispersion was stored at 20°C for 14 days and then transferred to another container. The state at this time was visually checked. Dispersion 1 did not drip and the entire amount could be transferred. Dispersion 2 and 3 dripped, but the entire amount could still be transferred. Dispersion 4 dripped, and residual solids remained in the original container, so the entire amount could not be transferred.
[0086] 3. Example of manufacturing laminate The dispersion 1 obtained in the above Example 1 was applied to the surface of a long film (thickness 34 μm) of a polyimide containing 1,4-bis(4-aminophenoxy)benzene and 4,4'-diaminobenzanilide as diamine-based units by a rod coating method to form a liquid film. Thereafter, the polyimide film formed with the liquid film was passed through a drying furnace at 120°C for 5 minutes and dried by heating to obtain a dry film. Thereafter, the dry film was heated at 380°C for 3 minutes in a nitrogen furnace. The same treatment was also applied to the other surface of the polyimide film to produce a laminate 1 having a polyimide film and a polymer layer (thickness 33 μm) of a molten sintered product containing F particles 1 on both surfaces thereof. Laminated body 2 was obtained in the same manner except that dispersion 1 was changed to dispersion 2, laminated body 3 was obtained in the same manner except that dispersion 1 was changed to dispersion 3, and laminated body 4 was obtained in the same manner except that dispersion 1 was changed to dispersion 4. The surface state of the polymer layer of each laminate was confirmed, and it was found that the laminated body 1, laminated body 2, laminated body 3, and laminated body 4 were ranked in order of the least amount of streaks and cracks. Possibility of industrial application
[0087] The dispersion obtained by this method is excellent in dispersion stability and handling properties. In addition, a molded product having highly developed physical properties of the F polymer, particularly excellent surface appearance, can be formed, specifically a laminate having a polymer layer formed from the dispersion.
[0088] In addition, the entire contents of the specification, claims, and abstract of Japanese Patent Application No. 2022-094393 filed on Jun. 10, 2020 are cited herein as a disclosure of the present specification.
Claims
1. A method for producing a dispersion liquid, wherein a liquid having a density of 1.15 to 1.5 g / cm is subjected to a wet bead mill. 3 A liquid composition containing particles of a tetrafluoroethylene-based polymer and a liquid dispersion medium is treated to obtain a dispersion containing particles of the tetrafluoroethylene-based polymer.
2. The manufacturing method according to claim 1, wherein: The average particle size of the tetrafluoroethylene polymer particles is less than 10 μm, and the specific surface area is 1 to 25 m 2 / g.
3. The manufacturing method according to claim 1, wherein: The content of the tetrafluoroethylene polymer particles is greater than 30% by mass.
4. The manufacturing method according to claim 1, wherein: The liquid dispersion medium is at least one selected from the group consisting of water, amides, ketones, and esters.
5. The manufacturing method according to claim 1, wherein: The liquid composition further contains a water-soluble solvent having a surface tension of 20 to 30 mN / m.
6. The manufacturing method according to claim 1, wherein: The viscosity of the liquid composition is 100 to 10000 mPa·s.
7. The manufacturing method according to claim 1, wherein: The surface tension of the liquid composition is 15-45 mN / m.
8. The manufacturing method according to claim 1, wherein: The liquid composition is prepared by mixing the tetrafluoroethylene polymer powder with the liquid dispersion medium.
9. The manufacturing method according to claim 8, wherein: During the preparation of the liquid composition, a degassing treatment is performed.
10. The manufacturing method according to claim 1, wherein: The treatment by the wet bead mill uses beads with a diameter of 2 mm or less and is selected from any of batch, through or circulating bead mills.
11. The manufacturing method according to claim 1, wherein: The dispersion after the wet bead mill treatment is further mixed with at least one of a liquid dispersion medium, an aromatic polymer, or an inorganic filler.
12. A dispersion obtained by a wet bead mill, wherein the concentration of particles having a particle size of 60 μm or more as measured by a particle analyzer is less than 1,000 particles / ml, and the dispersion comprises particles of a tetrafluoroethylene polymer and a liquid dispersion medium.
13. The dispersion according to claim 12, wherein The content of the tetrafluoroethylene polymer particles is greater than 30% by mass and less than 75% by mass.
14. A method for producing a laminate, comprising placing a dispersion obtained by the method according to any one of claims 1 to 11 on a substrate surface and heating the dispersion to form a polymer layer containing the tetrafluoroethylene polymer, thereby obtaining a laminate having a substrate layer composed of the substrate and the polymer layer in this order.
15. The manufacturing method according to claim 14, wherein: The substrate is a polyimide film, which contains at least two diamine units derived from 1,4-bis(4-aminophenoxy)benzene and 4,4'-diaminobenzanilide, has a dielectric constant of less than 3.5 at 5.8 GHz, a dielectric loss tangent of less than 0.006, a water absorption of less than 1.2%, and a linear expansion coefficient of 2 to 18 ppm / °C at 50 to 200°C.
Citation Information
Patent Citations
Method for producing aqueous dispersion and aqueous dispersion
JP2008260864A
Remote control system
JP2022094393A
Fluororesin composition, fluororesin sheet, multilayer body and substrate for circuits
WO2020145133A1